Efficiency of a compact CO2 coaxial plasma torch driven by ultrafast microwave power pulsing: Stability and plasma gas flow dynamics. (April 2022) - Soldatov, S.; Carbone, E.; Kuhn, A.; Link, G.; Jelonnek, J.; Dittmeyer, R.; Navarrete, A.
Abstract: Ultrafast pulsation of microwave power for CO2 conversion using plasmas is a mean to improve the efficiency of the process. Nevertheless, the fundamental phenomena involved need deeper understanding in order to design optimal plasma based devices. Therefore, detailed parametric scans of the plasma torch performance are performed with plasma diagnostics to unravel the underlying mechanisms limiting the CO yield. Very short pulsed plasmas have low CO2 conversion because of the energy cost needed to generate the plasma itself. For power pulses longer than 2–3 µs, excess energy is spent in gas heating up to 7000 K. Few µs (both ON and OFF times) have the best efficiency and gas temperatures of about 3000 K are measured at the beginning of the pulse. Power modulation and appropriate gas flow residence times allow dissociating CO2 also in the power-OFF phase and therefore to optimize the efficiency of the process. 2D cylindrical symmetric simulations of the plasma torch give insight in the gas flow dynamics and estimation for a gas residence time in the plasma volume. The gas in the regimes with OFF times close to or longer than the residence time leads to under-processing of the CO2 flow. The plasma is destabilized by the gas flow itself depending on pulsed regime. The combination of capacitive coupling for ignition (confirmed by frequency harmonics generation) and inductive power absorption lead to complex plasma dynamics. Highlights: Phenomena occurring in atmospheric pulsed microwave plasmas are studied. The used commercial torch enables quenching, but it restricts gas conversion. In optimal pulse regimes, plasma is often destabilized by the gas flow itself. Temporal variation of the absorbed microwave power depends on plasma conditions. Interplay between power pulsing and gas flow parameters is important.